Islamic Work Ethics-Based Organizational Citizenship Behavior to Improve the Job Satisfaction and Organizational Commitment of Higher Education Lecturers in Indonesia - Farid Riadi; Dini Riani; Denok Sunarsi; Afzal Sayed Munna (Har Press Indonesia, 2025)
The issue of Organizational Citizenship Behavior (OCB) among academics, especially lecturers, plays a vital role in assessing the quality and performance of higher education institutions. This study explores how Islamic work ethics, job satisfaction, and organizational commitment contribute to the development of OCB among lecturers. A total of 365 lecturers from 14 private universities were selected using proportional random sampling. The research applied Structural Equation Modeling (SEM) with the AMOS software to analyze the data. The results demonstrate that Islamic work ethics have a significant and positive effect on both OCB and organizational commitment. However, the influence of Islamic work ethics on job satisfaction, while positive, is statistically insignificant. Moreover, job satisfaction is found to have a strong and significant impact on OCB, but its relationship with organizational commitment remains insignificant. These findings reveal a nuanced interaction between ethical values, personal satisfaction, and voluntary behavior within the academic work environment. Given these insights, the study highlights the importance of fostering Islamic work ethics and job satisfaction to improve OCB among lecturers. Strengthening these elements may not only elevate individual performance but also enhance organizational commitment over time. As a practical implication, private university management should prioritize ethical development programs and support systems that improve job satisfaction. Such initiatives are expected to contribute to a more engaged, committed, and ethically grounded academic workforce, ultimately advancing institutional quality and effectiveness.